Expanding the chemical diversity of natural esters by engineering a polyketide-derived pathway into Escherichia coli - Menendez-Bravo, Simón Matías (2014)
Microbial fatty acid (FA)-derived molecules have emerged as promising alternatives to petroleum-based chemicals for reducing dependence on fossil hydrocarbons. However, native FA biosynthetic pathways often yield limited structural diversity, and therefore restricted physicochemical properties, of the end products by providing only a limited variety of usually linear hydrocarbons. Here we have engineered into Escherichia coli a mycocerosic polyketide synthase-based biosynthetic pathway from Mycobacterium tuberculosis and redefined its biological role towards the production of multi-methyl-branched-esters (MBEs) with novel chemical structures. Expression of FadD28, Mas and PapA5 enzymes enabled the biosynthesis of multi-methyl-branched-FA and their further esterification to an alcohol. The high substrate tolerance of these enzymes towards different FA and alcohol moieties resulted in the biosynthesis of a broad range of MBE. Further metabolic engineering of the MBE producer strain coupled this system to long-chain-alcohol biosynthetic pathways resulting in de novo production of branched wax esters following addition of only propionate.